2015
DOI: 10.1093/rpd/ncv441
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSMENT OF THE LOCAL EXPOSURE OF SKIN ON HANDS OF NUCLEAR MEDICINE WORKERS HANDLING18F-LABELLED RADIOPHARMACEUTICALS: PRELIMINARY CZECH STUDY

Abstract: The article summarises some preliminary results of the assessment of the exposure of hands of workers manipulating F-labelled radiopharmaceuticals based on personal monitoring at two nuclear medicine clinics in the Czech Republic. The measurements were carried out using special thermoluminescence dosemeters the readings of which could be interpreted in terms of the personal dose equivalent H(0.07) approximating the equivalent dose to the skin at various locations on the surface of both hands. The results have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Figure 3. The findings of the ORAMED study, which included seven European countries, illustrates that the skin exposure can exceed the relevant dose limit in about 20 % of radiation workers in nuclear medicine [7].…”
Section: Specific Problems Of Skin Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3. The findings of the ORAMED study, which included seven European countries, illustrates that the skin exposure can exceed the relevant dose limit in about 20 % of radiation workers in nuclear medicine [7].…”
Section: Specific Problems Of Skin Exposurementioning
confidence: 99%
“…Since skin exposure presents a special case as regards achieving compliance with the regulatory requirements, some more detailed measurements have been carried out in selected nuclear medicine clinics in the Czech Republic [7]. The measurements were carried out using special TLDs, the readings of which could be interpreted as the equivalent dose to the skin.…”
Section: Specific Problems Of Skin Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Twenty years ago, for the concerns raised by the radiation energy of the highly penetrating 511 keV annihilation photons, the first study of personnel dosimetry in positron emission tomography (PET) found that the effective radiation doses to technologists in PET centres (mostly carrying out 18 F-FDG studies) were within recommended occupational radiation protection guidelines [4], and since then, comparatively little attention has been paid to the problem of operator exposure.…”
mentioning
confidence: 99%
“…In a study that used high-sensitivity TLD detectors placed on the fingertips of both hands and attached at the level of eye lenses and thyroid to assess equivalent doses to staff members, the highest dose was measured during the administration of 18 F-FDG to the patients and during the preparation of 18 F-FDG, the most exposed body parts being the tips of the thumb, index, and middle fingers [11]. The data from this study suggest that in a PET centre running 1500 18 F-FDG scans per year, and using approximately 200 MBq per patient, the annual occupational equivalent dose to the fingers due to the fractionation of the radiopharmaceutical in a dedicated hot cell would not exceed 100 mSv.…”
mentioning
confidence: 99%